Water-based self-adhesive coating for electrical steel and preparation method of water-based self-adhesive coating

By adding organic polymer particle fillers and water-based film-forming resins to self-bonding coatings to form a three-dimensional network structure coating, the problems of glue overflow and stamping properties of self-bonding coatings in the field of new energy electric drives are solved, and the coating performance of high insulation, high adhesion and good stamping properties is achieved. It is suitable for micro motors, servo motors, automotive electric drives and wind turbines.

CN120682682APending Publication Date: 2025-09-23SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510982414.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing self-adhesive coatings in the field of new energy electric drives have problems such as glue overflow during secondary curing of the iron core, short life of the stamping die, and poor dimensional accuracy of the punching sheets, making it difficult to meet the requirements of high fastening strength and high stamping performance.

Method used

A water-based self-adhesive coating containing thermosetting water-based film-forming resin, organic polymer particle filler, additives and solvent is used. By adding organic polymer particle filler as a skeleton support and combining water as the main dispersion medium, an excellent three-dimensional network structure coating is formed to avoid glue overflow and improve stamping properties.

Benefits of technology

A self-adhesive coating with high insulation, high adhesion, no edge overflow and good stamping properties is achieved, which meets the high stamping precision and long-life die requirements in the new energy electric drive field and expands the application scope of self-adhesive coating products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005503329070000111
    Figure BDA0005503329070000111
  • Figure BDA0005503329070000121
    Figure BDA0005503329070000121
  • Figure BDA0005503329070000122
    Figure BDA0005503329070000122
Patent Text Reader

Abstract

The invention belongs to the technical field of metal surface coatings, and particularly relates to a water-based self-adhesive coating for electrical steel and a preparation method. The water-based self-adhesive coating for the electrical steel, provided by the invention, comprises the following components in percentage by weight: 1-70% of thermosetting water-based film-forming resin, 1-50% of organic polymer particle filler, 5-25% of auxiliaries and solvents and the balance of water. The water-based self-adhesive coating for the electrical steel, provided by the invention, can be used for producing a self-adhesive coating product which is high in insulation, high in adhesive force, free of edge overflow and good in stamping property, can be used for improving the use conditions of a user in an electrical steel plate stamping process and an iron core curing forming process, and expands the application of the self-adhesive insulating coating product for the electrical steel in the field of new energy electric drive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface coatings, and particularly relates to a water-based self-adhesive coating for electrical steel and a preparation method thereof. Background Art

[0002] Typically, electrical steel sheets are coated with an insulating coating, then stamped into a predetermined shape, stacked, and joined together through welding, bolts, snaps, or rivets to form a motor core. However, these cores are fixed using a localized "point" method, resulting in weak connection strength and insufficient for cores requiring higher fastening strength. This is why self-bonding technology has emerged. A self-bonding coating is applied to the surface of electrical steel strips, allowing the sheets to be bonded together using a "surface" method to form the core. This "surface" bonding method offers advantages such as high fastening strength, low magnetic vibration noise, and high motor efficiency. It is particularly suitable for applications where other fastening methods would result in distortion or insufficient rigidity, or where bolting, riveting, or welding is inconvenient.

[0003] Currently, self-bonding coatings are applied to continuously running steel strips by roller coating or spraying. After curing in a drying oven using open flames or hot air for a specified period of time, the self-bonding coating forms. The dry film thickness is typically controlled between 4μm and 8μm. During the motor manufacturing process, the electrical steel sheets coated with the self-bonding coating undergo a secondary core curing process. Typical process conditions are 180-250°C, a pressure load of 6-30 bar, and a holding time of 1-4 hours. This results in a core with excellent mechanical strength and rigidity. Existing self-bonding coatings are typically based on thermosetting epoxy resins and their curing agents. These coatings offer high dielectric strength, excellent corrosion resistance, excellent punchability, and strong bonding strength. Representative products include the Remisol EB546 and EB548 series of coatings manufactured by Rembrandtin. China Baoshan Iron & Steel Co., Ltd. also has a related patent application, patent number ZL200410017997.8, which discloses a water-based self-bonding coating for electrical steel. The coating contains a water-based epoxy resin emulsion, a curing agent, an accelerator, and various additives. Ningbo Tengguang New Materials Co., Ltd. has patent number ZL202210863339.9, which discloses a self-bonding coating for silicon steel containing E-44 epoxy resin, acrylic resin, isocyanate, and various additives.

[0004] However, the application process of this type of conventional self-adhesive coating has the following problems: during the core stacking and molding process, the self-adhesive coating is prone to glue overflow during secondary curing, and an additional core edge polishing process is required, resulting in low market acceptance of self-adhesive coating products.

[0005] In order to solve the problem of glue overflow in the application of self-adhesive coatings, a large number of technologies for adding inorganic fillers to self-adhesive coatings have emerged in China.

[0006] Ma'anshan Honghe Industrial Co., Ltd., patent number ZL201510546858.2, discloses an environmentally friendly self-bonding coating for electrical steel. The coating contains a water-soluble acrylic resin, a water-based epoxy resin, a dicyandiamide curing agent, various additives, and a composite inorganic filler of fumed silica and sodium aluminum silicate. China Baoshan Iron & Steel Co., Ltd., patent number ZL201810275197.8, discloses a water-soluble, environmentally friendly self-bonding insulating coating for electrical steel. The coating contains a thermosetting water-based film-forming resin, a thermoplastic water-based film-forming resin, various additives, and solvents, and contains inorganic particles of at least one of TiO2, ZnO, SiO2, Al2O3, ZrO2, Fe3O4, CaCO3, and Cr2O3. Guangzhou Feisi Synthetic Materials Co., Ltd., with patent number ZL202211414419.2, discloses a water-based epoxy self-bonding coating for silicon steel sheets. The coating contains a water-based epoxy resin emulsion, a toughening material, and a curing agent. The toughening material is composed of nanocomposite cellulose fibers, nanoclay, and modified nano-CaCO3 in a specific ratio. Changzhou Jiuye Materials Technology Co., Ltd., with patent number ZL2L2411125055.5, discloses a self-bonding coating for amorphous silicon steel sheets. The coating contains a modified epoxy resin, a modified curing agent, nano-titanium dioxide, and various additives.

[0007] The inorganic filler plays the role of skeleton support in the coating. The coating is not easily squeezed out during the pressurized heating process of the secondary curing of the iron core, which effectively overcomes the problem of glue overflow in the application of self-adhesive coating.

[0008] In recent years, China's electric drive technology for new energy vehicles has rapidly advanced, resulting in increasingly thinner electrical steel sheets. The typical thickness of 0.50mm has now been reduced to 0.20mm, with some specialized applications requiring thicknesses as low as 0.10mm. However, the increasingly thinner electrical steel sheets lack sufficient core locking rigidity, and are susceptible to deformation during riveting and welding. Self-adhesive coatings, when applied on a "surface" basis, have become an effective way to improve the fastening strength of thinner electrical steel sheets, making them a promising future trend in new energy electric drive applications. However, the new energy vehicle electric drive sector also demands high stampability, requiring not only high dimensional accuracy for complex tooth-shaped punchings but also a long service life for composite punching dies. Conventional self-adhesive coatings containing only organic resins can meet these stamping requirements, but they are prone to glue overflow during secondary curing of the core. Self-adhesive coatings with inorganic fillers effectively prevent glue overflow, but introduce the added problem of poor stamping performance.

[0009] The inorganic filler, which acts as a framework, is extremely hard and constantly wears the die blade during the stamping process, quickly causing the sheet dimensions to fail to meet precision requirements. To address these limitations in self-adhesive coatings, the new energy electric drive sector urgently needs a self-adhesive coating that prevents secondary curing and overflow while also exhibiting excellent sheeting properties. Summary of the Invention

[0010] In order to solve the contradictory problems of glue overflow at the secondary curing hot-pressing edge of the iron core, short life of the stamping die and poor dimensional accuracy of the punching sheet in the application of existing coatings in the field of new energy electric drive, the present invention provides a water-based self-adhesive coating for electrical steel and a preparation method.

[0011] Specifically, the water-based self-bonding coating for electrical steel provided by the present invention comprises, by weight percentage, 1-70% of a thermosetting water-based film-forming resin, 1-50% of an organic polymer particle filler, 5-25% of an additive and a solvent, and the balance being water.

[0012] The above-mentioned water-based self-bonding coating for electrical steel comprises, by weight percentage, 20-40% of the thermosetting water-based film-forming resin and 5-20% of the organic polymer particle filler.

[0013] The above-mentioned water-based self-bonding coating for electrical steel, the thermosetting water-based film-forming resin includes an epoxy grafted acrylic resin and a curing agent, wherein the solid weight of the epoxy grafted acrylic resin accounts for 79-99% of the solid weight of the thermosetting water-based film-forming resin, and more preferably 88-96%.

[0014] In the above-mentioned water-based self-bonding coating for electrical steel, the curing agent is one or more of dicyandiamide, isocyanate, amino resin, organic hydrazide, and imidazole.

[0015] The above-mentioned water-based self-bonding coating for electrical steel, the preparation method of the epoxy grafted acrylic resin comprises the following steps:

[0016] (1) nitrogen is introduced into a reaction kettle, a low molecular weight bisphenol glycidyl ether epoxy resin is added, and the mixture is heated to 70-90° C., bisphenol raw material is added under stirring, and the temperature is raised to 160-190° C. for chain extension reaction, and the temperature is kept at this temperature for 2-3 hours. N-methylpyrrolidone is added, and the temperature is lowered to 100-130° C. to obtain a high molecular weight epoxy resin I with a relative molecular weight of 4000-15000;

[0017] (2) adding the pre-mixed acrylic acid monomer and free radical initiator dropwise into the reaction kettle of the high molecular weight epoxy resin I, and continuing to heat at 100-130° C. for 2-3 hours, cooling to 70-90° C., and stopping the nitrogen flow;

[0018] (3) Add deionized water and a neutralizing agent, stir at 40-50° C. for 0.5-2 hours, cool to room temperature and discharge to obtain epoxy grafted acrylic resin II.

[0019] In the above-mentioned water-based self-bonding coating for electrical steel, the epoxy grafted acrylic resin II has an epoxy equivalent of 300-5000 g / eq, a weight average molecular weight Mw of 4000-20000, and a hydroxyl value of 25-85 mgKOH / g.

[0020] The water-based self-bonding coating for electrical steel mentioned above has the low molecular weight bisphenol glycidyl ether epoxy resin, an epoxy equivalent of 100-300 g / eq, and a room temperature viscosity of 2000-15000 mPa·s.

[0021] In the above-mentioned water-based self-bonding coating for electrical steel, the bisphenol raw material is one or more of bisphenol A, bisphenol F, and bisphenol S.

[0022] In the above-mentioned water-based self-bonding coating for electrical steel, the weight ratio of the low molecular weight bisphenol glycidyl ether epoxy resin to the bisphenol raw material is 50-70:20-40.

[0023] In the above-mentioned water-based self-bonding coating for electrical steel, the weight ratio of the N-methylpyrrolidone to the low molecular weight epoxy resin is (7-10):(11-15).

[0024] In the above-mentioned water-based self-bonding coating for electrical steel, the weight ratio of the high molecular weight epoxy resin I to the acrylic monomer is 50-90:10-30.

[0025] The above-mentioned water-based self-bonding coating for electrical steel, the acrylic monomer includes at least one of acrylic acid and methacrylic acid, and styrene, and at least one of butyl acrylate, ethyl acrylate, methyl methacrylate, and β-hydroxyethyl acrylate; more preferably, methacrylic acid, styrene, and butyl acrylate; wherein the molar ratio of the three is 10-15:4-7:1.

[0026] In the above-mentioned water-based self-bonding coating for electrical steel, the neutralizer is any one of alkylamine, arylamine, and alkylolamine, and the weight ratio of the neutralizer to the acrylic acid monomer is (1-4): (6-10).

[0027] In the above-mentioned water-based self-bonding coating for electrical steel, the free radical initiator is one of a peroxide initiator and an azo initiator.

[0028] In the above-mentioned water-based self-bonding coating for electrical steel, the weight of the free radical initiator accounts for 3%-10% of the weight of the acrylic acid monomer, and more preferably 5%-8%.

[0029] In the above-mentioned water-based self-bonding coating for electrical steel, the organic polymer particle filler includes at least one of polystyrene, polyacrylonitrile, and polyvinylidene fluoride, and is more preferably a polystyrene copolymer, with a solid content of 30%-80% and a particle size of 0.3-3 μm.

[0030] In the above-mentioned water-based self-bonding coating for electrical steel, the auxiliary agent comprises at least one of a defoamer, a wetting agent, a leveling agent, a viscosity regulator, and a dispersant.

[0031] The above-mentioned water-based self-bonding coating for electrical steel, the solvent includes at least one of ethanol, propanol, ethylene glycol, glycerol, isopropyl alcohol, propylene oxide, n-butanol, isobutanol, ethylene glycol methyl ether, ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and propylene glycol phenyl ether.

[0032] The present invention also provides a method for preparing the above-mentioned aqueous self-bonding coating for electrical steel, comprising: uniformly stirring a thermosetting aqueous film-forming resin, an organic polymer particle filler, an auxiliary solvent and water according to a proportion.

[0033] The technical solution of the present invention has the following beneficial effects:

[0034] (1) The water-based self-adhesive coating for electrical steel provided by the present invention can produce self-adhesive coating products with high insulation, high adhesion, no edge overflow and good stamping properties, which can improve the user conditions in the electrical steel plate stamping process and the iron core curing and forming process, and expand the application of electrical steel self-adhesive insulation coating products in the field of new energy electric drive.

[0035] (2) The water-based self-bonding coating for electrical steel provided by the present invention, by adding organic polymer particle fillers, makes the obtained self-bonding coating film have a film thickness of 2-8 μm, and has extremely high bonding strength (3-8 N / mm) and insulation performance (surface insulation resistance ≥ 50Ω·cm2 / sheet) in the C stage, while obtaining excellent corrosion resistance (5% NaCl-35℃-6h, rust area ≤ 2%), resistance to chemical solvents (common alcohols, hydrocarbons, ketones and water insoluble), and heat resistance (long-term heat resistance of 180℃). The excellent coating performance can fully meet the application of high insulation and strong bonding motor cores, especially in the fields of micro motors, servo motors, automotive electric drives, wind power generators, etc. At the same time, it has excellent stamping properties in the B stage, can effectively lubricate the die, improve the die life, ensure the dimensional accuracy of the punching sheet and reduce the burrs of the punching sheet, prevent short circuits between the stacked sheets and reduce the stacking coefficient, and meet the high stamping accuracy and long die life requirements in the new energy field. In addition, when the core is stacked and secondary solidified, there will be no self-adhesive coating overflow on the edge of the core punching sheet, which reduces the additional glue removal work on the core edge and improves the core processing efficiency.

[0036] (3) The water-based self-bonding coating for electrical steel provided by the present invention is based on a water-dispersible film-forming resin and an organic polymer particle filler, with water as the main dispersion medium. The organic solvent content is low, and solvents with low harm to the human body are selected. The final coating product is a low-VOC, non-flammable, non-hazardous product, which belongs to the environmentally friendly coating series. It is relatively friendly to human health and the surrounding environment in the large-scale production and later industrial application of the coating. Combined with its excellent coating performance, it has huge room for commercial application in the future. DETAILED DESCRIPTION

[0037] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.

[0038] Specifically, the water-based environmentally friendly self-adhesive insulating coating for electrical steel provided by the present invention includes a thermosetting water-based film-forming resin, an organic polymer particle filler, an additive, a solvent and pure water.

[0039] The present invention's water-based, environmentally friendly, self-adhesive insulating coating for electrical steel is based on a water-dispersible film-forming resin and organic fillers, with water as the primary dispersion medium and a low organic solvent content. It is friendly to human health and the surrounding environment, and belongs to a series of environmentally friendly coatings. Furthermore, the coating formed by this coating exhibits excellent protective properties, high insulation, and high adhesion. This solves the conflicting issues of existing self-adhesive coatings in the new energy electric drive field, such as adhesive overflow at the hot-pressed edges of the iron core and poor sheeting during the stamping process. This expands the application of self-adhesive insulating coatings for electrical steel in this field.

[0040] Preferably, the solid weight of the thermosetting water-based film-forming resin accounts for 1-70% of the total weight of the coating, the solid weight of the organic polymer particle filler accounts for 1-50% of the total weight of the coating, the weight of the additives and solvents accounts for 5-25% of the total weight of the coating, and the rest is pure water.

[0041] More preferably, the solid weight of the thermosetting water-based film-forming resin accounts for 20-40% of the total weight of the coating.

[0042] More preferably, the solid weight of the organic polymer particle filler accounts for 5-20% of the total weight of the coating.

[0043] Wherein, the thermosetting water-based film-forming resin comprises epoxy grafted acrylic resin and a curing agent.

[0044] Preferably, the solid weight of the epoxy grafted acrylic resin accounts for 79-99% of the solid weight of the thermosetting water-based film-forming resin, and more preferably 88-96%.

[0045] Wherein, the curing agent is one or more of dicyandiamide, isocyanate, amino resin, organic hydrazide and imidazole.

[0046] The preparation method of the epoxy grafted acrylic resin adopted in the present invention is as follows:

[0047] (1) Nitrogen is introduced into a reaction kettle, and the desired low molecular weight epoxy resin is added and heated to 70-90°C. A bisphenol raw material is added while stirring, and the reaction is heated to 160-190°C for chain extension reaction. The reaction is kept at this temperature for 2-3 hours, and N-methylpyrrolidone is added. The reaction is cooled to 100-130°C to obtain a high molecular weight epoxy resin I with a relative molecular weight of 4000-15000.

[0048] (2) Add the pre-mixed acrylic acid monomer and free radical initiator to the reaction kettle of the high molecular weight epoxy resin I at a uniform rate, and add the mixture to the reaction kettle over a period of 1-3 hours. Continue to heat the mixture at 100-130°C for 2-3 hours, cool the mixture to 70-90°C, and stop the nitrogen flow.

[0049] (3) adding deionized water and a neutralizing agent, stirring at 40-50° C. for about 0.5-2 hours, cooling to room temperature, and discharging to obtain an epoxy grafted acrylic resin II having an epoxy equivalent of 300-5000 g / eq, a weight average molecular weight Mw of 4000-20000, and a hydroxyl value of 25-85 mgKOH / g.

[0050] Preferably, the low-molecular-weight epoxy resin is a bisphenol-type glycidyl ether epoxy resin with an epoxy equivalent weight of 100-300 g / eq and a room-temperature viscosity of 2000-15000 mPa·s. The bisphenol raw material is one or more of bisphenol A, bisphenol F, and bisphenol S, more preferably bisphenol A, with the weight ratio of the two being 50-70:20-40. The weight ratio of N-methylpyrrolidone to the low-molecular-weight epoxy resin is (7-10):(11-15). A high-molecular-weight epoxy resin I with a predominantly linear structure is obtained through a chain extension reaction.

[0051] Preferably, the weight ratio of high molecular weight epoxy resin I to acrylic monomer is 50-90:10-30. By using the graft copolymerization method, the carboxyl-containing comonomer is grafted onto the high molecular weight epoxy resin I molecule, which ensures the water dispersibility of the resin and improves the toughness of the epoxy resin.

[0052] Preferably, the acrylic monomer comprises at least one of acrylic acid and methacrylic acid, styrene, and at least one of butyl acrylate, ethyl acrylate, methyl methacrylate, and β-hydroxyethyl acrylate. More preferably, methacrylic acid, styrene, and butyl acrylate are present in a molar ratio of 10-15:4-7:1, ensuring that the grafted side chains contain two carboxyl groups for every three acrylic monomer units, thereby ensuring the water dispersibility of the epoxy resin.

[0053] Preferably, the free radical initiator is a peroxide initiator or an azo initiator, more preferably a peroxide initiator. The free radicals of this type of initiator can transfer hydrogen from the secondary or tertiary carbon in the bisphenol resin, and then initiate the monomer to produce a graft copolymer.

[0054] Preferably, the weight of the free radical initiator accounts for 3%-10% of the weight of the acrylic acid monomer, more preferably 5%-8%. In practice, when the initiator amount is less than 3%, an effective grafting reaction cannot be guaranteed. When the initiator amount exceeds 10%, polymerization of the acrylic acid free monomer is accelerated, which is not conducive to grafting and ultimately cannot ensure the water dispersibility of the epoxy resin.

[0055] Preferably, the neutralizing agent is any one of alkylamine, arylamine, and alkylolamine, and more preferably alkylolamine, such as dimethylethanolamine.

[0056] Preferably, the weight ratio of the neutralizing agent to the acrylic acid monomer is (1-4): (6-10). The present invention obtains an extremely stable aqueous dispersion by using an amine alkaline substance to neutralize the carboxyl group grafted onto the epoxy resin.

[0057] Preferably, the organic polymer particle filler component is at least one of polystyrene, polyacrylonitrile, and polyvinylidene fluoride, and more preferably a polystyrene copolymer, which has excellent chemical resistance, weather resistance, heat resistance, and impressive mechanical strength.

[0058] Preferably, the organic polymer filler is a water dispersion with a solid content of 30%-80% and a particle size of 0.3-3 μm. It plays the role of a skeleton support in the coating. The coating is not easily squeezed out during the secondary heating and pressurization of the iron core, effectively overcoming the problem of glue overflow in the application of self-adhesive coatings. At the same time, the organic filler has a low hardness and will not cause adverse damage to the die during the stamping process, thereby ensuring the dimensional accuracy of the punching sheet and meeting the demand for high punching performance in the new energy electric drive field.

[0059] Preferably, the auxiliary agent comprises at least one of a defoamer, a wetting agent, a leveling agent, a viscosity regulator, and a dispersant.

[0060] Preferably, the solvent comprises at least one of ethanol, propanol, ethylene glycol, glycerol, isopropyl alcohol, propylene oxide, n-butanol, isobutanol, ethylene glycol methyl ether, ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and propylene glycol phenyl ether.

[0061] The present invention has found that when the thermosetting water-based film-forming resin is applied alone on an electrical steel substrate and rapidly baked to form a film, it becomes a semi-cured state, i.e., in the B stage. At this point, only the solvent and water are completely volatilized, and part of the epoxy resin and a small amount of curing agent are heated and cross-linked to form a film. A large amount of uncured activated epoxy resin and latent curing agent are still present in the film, and the chemical solvent resistance is poor. Under the conditions of secondary heating in the later stage, it is converted into a liquid form again. The remaining activated resin and curing agent continue to cross-link to form a network structure, achieving full curing. After that, the form no longer transforms and no longer reacts when heated again, i.e., the C stage. Therefore, after the coated punching sheet with the B stage is heated and pressurized for the second time, a bonding effect is generated between the coatings, firmly fixing the punching sheet into an iron core. At this point, the coating film has a three-dimensional network structure, excellent bonding, insulation, mechanical strength, chemical solvent resistance, adhesion and certain heat resistance. However, as mentioned above, when the active resin form is converted into a liquid again during the secondary heating of the B stage, it is impossible to avoid the phenomenon of glue overflow at the edge of the coated punching sheet.

[0062] In view of the defect of overflow of thermosetting water-based film-forming resins during secondary heating, the present invention adds an organic polymer particle filler, which is composed of at least one of polystyrene, polyacrylonitrile, and polyvinylidene fluoride, and is more preferably a polystyrene copolymer, which has excellent mechanical strength, chemical solvent resistance, and heat resistance. At the same time, the particle size is required to be 0.3-3μm, and the solid weight accounts for 5%-20% of the total weight of the coating, and it mainly plays a skeleton support role in the coating. Although the retained part of the activated resin in stage B is converted into liquid form during the secondary heating of the iron core, the organic filler with excellent heat resistance plays a supporting role and can withstand a certain degree of deformation resistance. Therefore, the liquid resin is not squeezed and is not easy to overflow, which effectively overcomes the problem of overflow in the application of self-adhesive coatings.

[0063] In practice, it has been shown that particle sizes too small (≤ 0.3μm) and a content too low (≤ 5%) will not provide a supporting coating skeleton and effectively address the self-adhesive overflow problem. Particle sizes too large (≥ 3μm) and a content too high (≥ 20%) will reduce the bond strength between the self-adhesive coating sheets and may even cause surface powdering, hindering subsequent stamping operations. Furthermore, organic particle fillers have a lower hardness and, unlike inorganic fillers, will not damage the stamping die during the stamping process, reducing die life. This ensures high-speed stamping of thin-gauge products in the new energy electric drive sector.

[0064] The main function of the additives in the coating of the present invention is to ensure the workability of the water-based coating, meet the operation requirements of high-speed spraying or roller coating, adapt to the continuous production requirements of electrical steel strip, and avoid possible surface defects of the coating such as bubbles, wetting, and flow. The main function of the organic solvent in the coating is to promote the solubility of the epoxy resin and additives in water, avoiding the occurrence of abnormal viscosity peaks when the coating liquid is diluted with water; at the same time, it reduces the surface tension of the coating liquid, improves the infiltration of the electrical steel substrate, and avoids the occurrence of defects such as shrinkage holes, bubbles, and coating leaks during the coating liquid application and baking process, which may even affect the adhesion between the coating and the substrate.

[0065] By adding pure water to the coating of the present invention, the solid content of the final coating product can be adjusted to 30-60%, and the coating viscosity can be controlled to 20-80 seconds (T4), so as to meet the control of the coating film thickness in different coating methods.

[0066] The electrical steel strip coated on both sides with the self-adhesive coating provided by the present invention is cured by baking at a plate temperature of 130-250°C, and the thickness of the single-sided coating film is 2-8μm. The coated electrical steel strip is punched and stacked into an iron core, and the secondary curing process is: at a temperature of 130-220°C and a load pressure of 5-20Bar for 0.5-4 hours, and the preferred process is at a temperature of 160-200°C and a load pressure of 8-15Bar for 0.5-3 hours. Through the above application process, the self-adhesive coating of the present invention realizes self-adhesion between the iron core punching sheets, and its strength fully meets the requirements for iron core fixation.

[0067] Example

[0068] The present invention is further illustrated by way of examples below, but the invention is not limited to the scope of the examples. The experimental methods in the following examples where specific conditions are not specified were based on conventional methods and conditions. The raw materials used in the following examples were all commercially available.

[0069] When preparing water-based self-bonding coatings for electrical steel in the Examples and Comparative Examples, the components were mixed and stirred uniformly according to the proportions. The raw materials and proportions are shown in Tables 1 and 2. In the Comparative Examples, when inorganic fillers were used, they were pre-dispersed in pure water at high speed and then added to the coating system as a dispersion.

[0070] The preparation methods of the epoxy resin I and epoxy grafted acrylic resin II used in the embodiments and comparative examples are as follows:

[0071] (1) Nitrogen was introduced into a reactor, and 15 kg of bisphenol-type glycidyl ether epoxy resin (purchased from Dow DER 331) was added and heated to 85°C. 7 kg of bisphenol A was added while stirring, and the reaction was heated to 187°C for chain extension. The reaction was kept at this temperature for 2.5 hours, and 12 kg of N-methylpyrrolidone was added. The reaction was cooled to 120°C to obtain a high molecular weight bisphenol A epoxy resin I.

[0072] (2) 6.0 kg of methacrylic acid, 3.3 kg of styrene, 0.7 kg of butyl acrylate, and 0.67 kg of benzoyl peroxide were premixed and added dropwise to the reactor at a uniform rate over 2 hours. The mixture was kept at 120°C for 2.5 hours, cooled to 83°C, and the nitrogen atmosphere was stopped.

[0073] (3) 11 kg of deionized water and 3.6 kg of dimethylethanolamine were added, and the mixture was stirred at 50° C. for approximately 1 hour. The mixture was cooled to room temperature and discharged to obtain epoxy grafted acrylic resin II. Testing revealed that the epoxy grafted acrylic resin II had an epoxy equivalent weight of 4100 g / eq, a weight-average molecular weight (Mw) of 7500, and a hydroxyl value of 35 mgKOH / g.

[0074] For comparison purposes, all coating solutions were controlled at a solids content of 40-50% and a viscosity of 20-30 seconds (T4). The coating solution was applied to 30WD1500 electrical steel strip for new energy electric drive applications by roller coating and dried using infrared or hot air at a plate temperature of 130-250°C to form a B-stage coating with a dry film thickness of 5μm. Roller peel testing was performed, and the secondary curing process was maintained at a temperature of 160-200°C and a pressure load of 8-15 bar for 0.5-3 hours.

[0075] The evaluation results of the coating liquid and coating performance are shown in Table 3. The meanings of the evaluation symbols in Table 3 are as follows: ◎ excellent; ○ good; □ average; △ poor; × poor and unacceptable.

[0076] As shown in Table 3, the protective properties and insulation properties of the pure high molecular weight epoxy resin coating 1 (comparative example 1) without acrylic acid modification are good, but the flexibility and punching properties of the coating are poor, and the coating stability and water dispersibility are poor or even unacceptable; the protective properties, insulation properties, bonding properties and punching properties of the coating without adding organic polymer particle fillers (Comparative Example 2) are excellent, but the heat resistance and anti-overflow glue properties of the coating are poor; the pencil hardness, scratch resistance, heat resistance and anti-overflow glue properties of the coating with inorganic fillers (Comparative Example 3) are excellent, but the coating density is poor, resulting in salt spray corrosion resistance and poor insulation, especially unacceptable punching properties; the comprehensive performance of the coatings of Examples 1-3 is good, especially the applicability (bonding strength, anti-overflow glue, punching properties) of the coatings is good, among which Example 2 can obtain excellent applicability (bonding, anti-overflow glue, punching properties) and has excellent protective properties and insulation, and is the best embodiment.

[0077] Table 1

[0078]

[0079] Note: The symbol “*” indicates that the mass ratio of dicyandiamide to diacid hydrazide in the curing agent is 3:1.

[0080] Table 2

[0081]

[0082] Note: The symbol "**" indicates that the mass ratio of the additive to the solvent in component C is 1:100-200.

[0083] The symbol “***” means that the sum of components A+B+C+D is 100.

[0084] Table 3

[0085]

[0086]

[0087] Next, the present invention also compares the effects of organic polymer particle fillers of different particle sizes on coating performance. In the preparation of water-based self-bonding coatings for electrical steel in each embodiment and comparative example, the components were mixed and stirred uniformly according to the proportions. The raw materials and proportions are shown in Tables 4 and 5.

[0088] For ease of comparison, the thermosetting water-based film-forming resin uses the same epoxy grafted acrylic resin II and curing agent, and the same organic polymer particle filler (polystyrene, purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.). Comparative Examples 5 and 7 are exactly the same as Example 2 in terms of ingredients and proportions, except for the different organic polymer filler particle sizes; Comparative Example 6 has the same filler particle size as Comparative Example 5, but the filler ratio is increased. For specific formulas, see Tables 4-5. The solid content of all coating liquids is controlled to 40-50%, and the coating viscosity is 20-30 seconds (T4). The coating liquid is applied to the surface of 30WD1500 electrical steel strip for new energy electric drive by roller coating, and dried by infrared or hot air at a plate temperature of 130-250°C to form a B-stage coating film with a dry film thickness controlled to 5μm. Secondary curing process: maintain a temperature of 160-200°C and a load pressure of 8-15Bar for 0.5-3 hours.

[0089] The evaluation results of the coating liquid and coating performance are shown in Table 6. As can be seen from Table 6, when the proportion of organic polymer fillers in the coating is the same, but the particle size is too small (Comparative Example 5), the filler cannot play an effective skeleton support role in the coating, and the coating's anti-glue overflow property deteriorates; in order to improve the anti-glue overflow property of the coating with small particle size fillers, the filler proportion can be increased to improve it (Comparative Example 6). The coating has good anti-glue overflow property, but the coating adhesion, corrosion resistance and bonding properties are significantly deteriorated or even unacceptable; when the organic polymer filler with a larger particle size is added (Comparative Example 7), the filler skeleton support effect is obvious, and the coating has excellent anti-glue overflow property, but it also leads to a deterioration in the density of the coating, and its corrosion resistance, insulation and bonding properties are significantly deteriorated or even unacceptable. It can be seen that in order to achieve excellent coating performance, there is a certain matching relationship between the particle size and proportion of the organic polymer filler in the coating.

[0090] Table 4

[0091]

[0092]

[0093] Note: The symbol “*” indicates that the mass ratio of dicyandiamide to diacid hydrazide in the curing agent is 3:1.

[0094] Table 5

[0095]

[0096] Note: The symbol "**" indicates that the mass ratio of the additive to the solvent in component C is 1:100-200.

[0097] The symbol “***” means that the sum of components A+B+C+D is 100.

[0098] Table 6

[0099]

[0100]

[0101] The present invention has been disclosed above with reference to preferred embodiments. However, those skilled in the art will appreciate that these embodiments are intended only to illustrate the present invention and are not to be construed as limiting the scope of the present invention. It should be noted that any equivalent variations and substitutions to these embodiments are to be considered encompassed within the scope of the claims of the present invention. Therefore, the scope of protection of the present invention shall be subject to the scope defined in the claims.

Claims

1. A water-based self-bonding coating for electrical steel, characterized in that: Calculated by weight percentage, it includes: 1-70% thermosetting water-based film-forming resin, 1-50% organic polymer particle filler, 5-25% additives and solvents, and the balance water; more preferably, 20-40% thermosetting water-based film-forming resin and 5-20% organic polymer particle filler.

2. The aqueous self-bonding coating for electrical steel according to claim 1, characterized in that: The thermosetting water-based film-forming resin comprises an epoxy grafted acrylic resin and a curing agent, wherein the solid weight of the epoxy grafted acrylic resin accounts for 79-99% of the solid weight of the thermosetting water-based film-forming resin, and more preferably 88-96%.

3. The aqueous self-bonding coating for electrical steel according to claim 2, characterized in that: The curing agent is one or more of dicyandiamide, isocyanate, amino resin, organic hydrazide and imidazole.

4. The aqueous self-bonding coating for electrical steel according to claim 1, characterized in that: The preparation method of the epoxy grafted acrylic resin comprises the following steps: (1) nitrogen is introduced into a reaction kettle, a low molecular weight bisphenol glycidyl ether epoxy resin is added, and the mixture is heated to 70-90° C., bisphenol raw material is added under stirring, and the temperature is raised to 160-190° C. for chain extension reaction, and the temperature is kept at this temperature for 2-3 hours. N-methylpyrrolidone is added, and the temperature is lowered to 100-130° C. to obtain a high molecular weight epoxy resin I with a relative molecular weight of 4000-15000; (2) adding the pre-mixed acrylic acid monomer and free radical initiator dropwise into the reaction kettle of the high molecular weight epoxy resin I, and continuing to heat at 100-130° C. for 2-3 hours, cooling to 70-90° C., and stopping the nitrogen flow; (3) Add deionized water and a neutralizer, stir at 40-50° C. for 0.5-2 hours, cool to room temperature and discharge to obtain epoxy grafted acrylic resin II.

5. The aqueous self-bonding coating for electrical steel according to claim 4, characterized in that: The epoxy grafted acrylic resin II has an epoxy equivalent of 300-5000 g / eq, a weight average molecular weight Mw of 4000-20000, and a hydroxyl value of 25-85 mgKOH / g.

6. The aqueous self-bonding coating for electrical steel according to claim 4, characterized in that: The low molecular weight bisphenol type glycidyl ether epoxy resin has an epoxy equivalent of 100-300 g / eq and a room temperature viscosity of 2000-15000 mPa·s; the bisphenol raw material is one or more of bisphenol A, bisphenol F, and bisphenol S; the weight ratio of the low molecular weight bisphenol type glycidyl ether epoxy resin to the bisphenol raw material is 50-70:20-40; and the weight ratio of the N-methylpyrrolidone to the low molecular weight epoxy resin is (7-10):(11-15).

7. The water-based self-bonding coating for electrical steel according to claim 4, characterized in that: The weight ratio of the high molecular weight epoxy resin I to the acrylic monomer is 50-90:10-30; the acrylic monomer comprises at least one of acrylic acid and methacrylic acid, and styrene, and at least one of butyl acrylate, ethyl acrylate, methyl methacrylate, and β-hydroxyethyl acrylate; more preferably, methacrylic acid, styrene, and butyl acrylate; wherein the molar ratio of the three is 10-15:4-7:1; the neutralizer is any one of an alkylamine, an arylamine, and an alkylolamine, and the weight ratio of the neutralizer to the acrylic monomer is (1-4):(6-10).

8. The aqueous self-bonding coating for electrical steel according to claim 4, characterized in that: The free radical initiator is one of a peroxide initiator and an azo initiator; the weight of the free radical initiator accounts for 3%-10% of the weight of the acrylic acid monomer, and more preferably 5%-8%.

9. The aqueous self-bonding coating for electrical steel according to claim 1, characterized in that: The organic polymer particle filler includes at least one of polystyrene, polyacrylonitrile, and polyvinylidene fluoride, and is more preferably a polystyrene copolymer, with a solid content of 30%-80% and a particle size of 0.3-3 μm; the auxiliary agent includes at least one of a defoamer, a wetting agent, a leveling agent, a viscosity regulator, and a dispersant; and the solvent includes at least one of ethanol, propanol, ethylene glycol, glycerol, isopropanol, propylene oxide, n-butanol, isobutanol, ethylene glycol methyl ether, ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and propylene glycol phenyl ether.

10. The method for preparing the aqueous self-bonding coating for electrical steel according to any one of claims 1 to 9, characterized in that: include: The thermosetting water-based film-forming resin, organic polymer particle filler, auxiliary agent solvent and water are mixed evenly according to the proportion.

Citation Information

Patent Citations

  • Environment-friendly self-bonding coating for electrical steel and preparing method thereof

    CN105131750A

  • Water-soluble environment-friendly self-bonding insulating coating for silicon steel

    CN110317532A

  • Silicon steel self-adhesive coating and process

    CN114989691A

  • Waterborne epoxy silicon steel sheet self-bonding coating and preparation method thereof

    CN115584186A

  • Self-bonding coating for amorphous silicon steel sheet and preparation method of self-bonding coating

    CN118772738A